Preformulation Characterization of Aqueous Extracts from The Leaves of Antimalarial Plants-Artemisia Annua L., Vernonia Amygdalina Del., And Microglossa Pyrifolia (Lam.) Kuntze - Angupale, Jimmy R.; Ajayi, Clement O.; Tusiimire, Jonans; Ngwuluka, Ndidi C. (International Journal of Applied Pharmaceutics, 2025)
Objective: The current study aimed at characterising relevant physical and chemical properties of antimalarial aqueous extracts from the leaves of Artemisia annua (Aa), Vernonia amygdalina (Va), and Microglossa pyrifolia (Mp) to build a solid foundation for the development of stable dosage forms. Methods: The aqueous extracts were profiled for key antimalarial chemical markers, aqueous solubility, partition coefficient, permeability, and powder flow properties using standard procedure with modifications where applicable. The powder compaction behaviours were studied using Kawakita and tablet ability models. Results: Aa extract had 11.2 % of total flavonoids and 0.27 % of artemisinin as its antimalarial chemical markers. Va and Mp extracts contained 0.07 % and 28.5 % total terpenoids as their respective chemical markers. All the extracts exhibited high solubility and low permeability, qualifying them as class III crude drugs based on the biopharmaceutical classification system (BCS). Mp had excellent flow (angle of repose 18.9, Hausner Ratio 1.2, and Carr’s Index 13 %) while Va and Aa had passable flow, thus requiring a glidant. The powder samples underwent plastic deformation, according to the Kawakita plot. Aa also showed the highest level of tabletability, followed by Va, and lastly, Mp (Area under curves of 18.5, 9.2, and 7.8 for Aa, Va and Mp, respectively). Conclusion: Based on their chemical and physical properties, the Aa, Va, and Mp aqueous extracts can be incorporated into stable, bioavailable, and modern herbal drug delivery systems or dosage forms.
Keywords: Preformulation; Physicochemical parameters; Tabletability; Artemisia annua; Vernonia amygdalina; Microglossa pyrifolia